The Digital Leadership of Educational Institution Administrators that Affect Teacher Skills in the 21st Century Co-Campus 1 Affiliated with the Secondary Educational Service Area Office Nakhon Sri Thammarat: The Digital Leadership of Educational Institution Administrators that Affect Teacher Skills in the 21st Century Co-Campus 1 Affiliated with the Secondary Educational Service Area Office Nakhon Sri Thammarat - Pengkong, jeerawan; Aunjanum, Santi (RATANABUTH JOURNAL, 2025)
Research on digital leadership of educational institution administrators that affects teacher skills in the 21st century, United Campus Group 1, under the Nakhon Si Thammarat Secondary Educational Service Area Office. The purpose of this research is to 1) study the level of digital leadership of educational institution administrators, 2) study the level of teacher skills in the 21st century, 3) study the relationship between Digital leadership of educational institution administrators and teacher skills in the 21st century 4) Study of digital leadership forecasting variables of educational institution administrators used to predict teacher skills in the 21st century using quantitative research. A sample of 260 people was obtained by determining the sample size from the Krejcie&. Morgan tables conducted a random sample of several samples The stratum used as a questionnaire had a confidence value of.98. Data analysis included frequency, percentage, mean, standard deviation. Pearson’s correlation coefficient and multiple correlation coefficients Then the data was analyzed. Summary and discussion of results The research results found that 1) Digital leadership of educational institution administrators Overall, it is at a high level. 2) Teacher skills in the 21st century are overall at the highest level. 3) Analysis of the relationship between the digital leadership level of educational institution administrators and teacher skills in the 21st century found that overall, there is a relationship plus at a high level Statistically significant at the level.01 4) Variables predicting the relationship between the level of digital leadership of educational institution administrators into the best predictive equation for predicting teacher skills in the 21st century. It was found that the best predictive variable When using the digital leadership variables of executives in 2 areas: citizenship in the digital age and development towards professionalism, able Together, the prediction of teacher skills in the 21st century was statistically significant at the.001 level. Both variables were able to explain the prediction of teacher skills in the 21st century by 55.3 percent